Iterated stochastic integrals and random velocity fluctuations - Yamamuro, Kouji (International Journal of Mathematics for Industry, 2023)
Iterated stochastic integrals of nonrandom integrands are constructed in the two-dimensional case. They are applied to the velocity fluctuations in a two-dimensional flow and mean kinetic energy of the velocity fluctuations is discussed.